2011
DOI: 10.1177/0192513x11406226
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Japanese Corporate Transnationalism on Men’s Involvement in Family Life and Relationships

Abstract: This study examines the ways in which Japanese corporate transnationalism affects husbands' involvement in family life and marital relationships primarily from a perspective of wives. It is based on interviews with 22 Japanese wives and 4 husbands. Studies of Japanese corporate transnationalism treat men as mere supervisors to local workers or representatives of corporations and pay little attention to their family relations. The study found that corporate transnationalism weakens the Japanese masculine corpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Consequent to the deportation, the mothers assume the responsibility of disciplining and providing finances to the family. This is similar to the Japanese phenomenon, which involves the shifting of the responsibility of household care and child care to mothers from fathers, who are transnational corporate workers and therefore remain away from home (Yasuike, 2011). In several cases, the participants in this study explained how deportation became a site of gender conflict as they no longer enjoy much authority in decision making, when it comes to the family or child care matters.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consequent to the deportation, the mothers assume the responsibility of disciplining and providing finances to the family. This is similar to the Japanese phenomenon, which involves the shifting of the responsibility of household care and child care to mothers from fathers, who are transnational corporate workers and therefore remain away from home (Yasuike, 2011). In several cases, the participants in this study explained how deportation became a site of gender conflict as they no longer enjoy much authority in decision making, when it comes to the family or child care matters.…”
Section: Discussionmentioning
confidence: 74%
“…Kilkey et al (2014), for example, argue that migrant men’s narratives about fathering remain embedded within a framework dominated by the division of labor. Yasuike (2011) found that the phenomenon of Japanese fathers who are transnational corporate workers with long absence from home, perpetuated the mother’s duty of taking care of their households and raising children single-handedly. However, no research has been conducted to suggest that a similar situation prevails in families whose fathers are separated from children by deportation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The phenomenon of “minimal fatherhood” or “absent fatherhood” is not exclusive to Hong Kong. Yasuike’s (2011) recent study, about Japanese fathers’ transition from being absent to being more involved, can best explain why children choose mothers to be the primary caregivers: Kimiyo [The mother] explained that when they were in their early teens, her children did not know how to interact with their father, who had mostly been absent when they were small, and that they kept an emotional distance from him. Likewise, Kimiyo’s husband did not know how to relate to his two sons as a father, besides providing for his family financially.…”
Section: How To Explain Children’s Preference Of Caretakers?mentioning
confidence: 99%
“…Kimiyo’s sons were rather annoyed by comments or criticisms from their father, who they felt knew nothing about their lives. (Yasuike, 2011, p. 17)…”
Section: How To Explain Children’s Preference Of Caretakers?mentioning
confidence: 99%
“…Overall, however, "traditional" conceptions of men as breadwinners still remain dominant in Japan (North 2009;Yasuike 2011). With the persisting culture of long working hours as one major reason, there is a significant gap between the time fathers and mothers spend with their offspring (Makino et al 2010).…”
Section: Introductionmentioning
confidence: 99%